Evaluasi Sistem Informasi Rekam Medis - Eka Megawati; Hudi Putra (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Medical records are files that contain records of documents regarding patient identity, examinations, treatment, actions and other services provided to patients. Medical records contain written or recorded information containing identity, anamnesis, support, diagnosis, services and medical actions that will be given to patients and treatment whether inpatient, outpatient or receiving emergency services (Permenkes RI No. 269 of 2008) . Increasing the effectiveness of recording medical record data accurately and quickly can take advantage of current technological advances through Electronic Medical Records (RME). Electronic Medical Records are Medical Records created using an electronic system intended for the maintenance of Medical Records